(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Flipping through the pages of the biography of Dr B R Ambedkar, we find a man of strong conviction and a leader par excellence in him. He wanted an egalitarian society in India, which had been the dream of every disadvantaged. He felt that education was one of the tools to achieve the long-cherished dream and emerged a man of vision and a leader of the marginalized. Dr Ambedkar had expressed his opinion about Indian education – from policy-making to managing educational institutions. Interestingly, he was the one who proposed privatization of educational facilities long ago. He presented his ideas logically to support his views and proposed to build up a nation with an Indian education system and technological advancement. This paper reflects on Ambedkar’s perspectives, and foresightedness on various aspects of Indian education like school education, life-long learning, inclusive education and privatization of educational facilities.